Urinary Kim-1 is a sensitive biomarker for the early stage of diabetic nephropathy in Otsuka Long-Evans Tokushima Fatty rats. (July 2014) - Hosohata, Keiko; Ando, Hitoshi; Takeshita, Yumie; Misu, Hirofumi; Takamura, Toshinari; Kaneko, Shuichi; Fujimura, Akio
Although urinary albumin is the well-known non-invasive marker for diabetic nephropathy, its sensitivity is relatively low. To select more adequate marker, we examined whether urinary tubular markers were more sensitive than albumin using spontaneous type 2 diabetic Otsuka Long-Evans Tokushima Fatty (OLETF) rats. The OLETF rats exhibited histopathological alterations in glomeruli and tubules at 14 weeks of age, but there were no significant differences in the urinary albumin between OLETF and control, Long-Evans Tokushima Otsuka (LETO), rats at 10–16 weeks of age. In the OLETF rats, urinary excretions of N-acetyl-β-d -glucosaminidase and neutrophil gelatinase–associated lipocalin did not increase at least until 20 weeks of age, and urinary vanin-1 transiently increased at 18 weeks of age. On the other hand, urinary kidney injury molecule-1 (Kim-1) in the OLETF rats significantly increased at 14 weeks of age, and the elevation continued up to 22 weeks of age. In a clinical study, urinary KIM-1 levels tended to be higher in type 2 diabetic patients with and without albuminuria than in control subjects. These results suggest that compared to urinary albumin, urinary Kim-1 is a more sensitive biomarker for the detection of early stage of nephropathy in these type 2 diabetic animals. Merit of urinary KIM-1 in diabetic patients remains to be determined.